2022
DOI: 10.3390/cancers14215279
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Characterization of the Regulatory Landscape of Adrenocortical Carcinoma: Novel Transcription Factors and Targets Associated with Prognosis

Abstract: We reconstructed a transcriptional regulatory network for adrenocortical carcinoma (ACC) using transcriptomic and clinical data from The Cancer Genome Atlas (TCGA)-ACC cohort. We investigated the association of transcriptional regulatory units (regulons) with overall survival, molecular phenotypes, and immune signatures. We annotated the ACC regulons with cancer hallmarks and assessed single sample regulon activities in the European Network for the Study of Adrenal Tumors (ENSAT) cohort. We found 369 regulons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 81 publications
(134 reference statements)
0
6
0
Order By: Relevance
“…Those studies have been made possible by accessing publicly available transcriptome databases to evaluate the intratumoral microenvironment. Using the RNA-seq and clinical data from 78 samples from the TCGA ACC cohort [ 118 ], Muzzi et al identified 369 regulatory units composed of a TF and its targets, named regulons, associated with OS in multivariate Cox analysis [ 119 ]. Of these 369 units, 346 were also significantly correlated to OS in the European Network for the Study of Adrenal Tumors (ENSAT) cohort with 44 ACC cases [ 120 ].…”
Section: Sf-1 and The Tumor Microenvironment (Tme) In Accmentioning
confidence: 99%
See 2 more Smart Citations
“…Those studies have been made possible by accessing publicly available transcriptome databases to evaluate the intratumoral microenvironment. Using the RNA-seq and clinical data from 78 samples from the TCGA ACC cohort [ 118 ], Muzzi et al identified 369 regulatory units composed of a TF and its targets, named regulons, associated with OS in multivariate Cox analysis [ 119 ]. Of these 369 units, 346 were also significantly correlated to OS in the European Network for the Study of Adrenal Tumors (ENSAT) cohort with 44 ACC cases [ 120 ].…”
Section: Sf-1 and The Tumor Microenvironment (Tme) In Accmentioning
confidence: 99%
“…Of these 369 units, 346 were also significantly correlated to OS in the European Network for the Study of Adrenal Tumors (ENSAT) cohort with 44 ACC cases [ 120 ]. The NR5A1 regulon represented one of the largest regulons in this analysis with 248 targets [ 119 ]. Overexpression of this TF correlated with low OS in the multivariate Cox and Kaplan–Meier analyses in the TCGA ACC cohort as well as in the ENSAT ACC cohort.…”
Section: Sf-1 and The Tumor Microenvironment (Tme) In Accmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, CENPA appears positively enriched in the WNT/β-Catenin signaling pathway and acts as the main regulon of Ki-67, a ubiquitous prognostic and proliferative marker widely employed in tumor histopathology ( 41 )(22/22). Herein, we reported that CENPA was up-regulated in PCa tissues, and its overexpression correlated with adverse clinicopathological outcomes in a large cohort ( 42 ).…”
Section: Discussionmentioning
confidence: 97%
“…The reconstruction of transcriptional regulatory networks based on regulatory hubs is a successful approach to investigating cancer biological mechanisms and elucidating drivers of tumor behavior 20–25 . This reverse‐engineering method is based on mutual information and can identify key regulatory elements that trigger a phenotype 26,27 .…”
Section: Introductionmentioning
confidence: 99%